Evaluating the User-Friendliness of a Mobile Application for Outpatient Food Monitoring: A System Usability Scale (SUS) Approach - Sulistiyono, Mulia; Habib Dwi Prajoto; Bernadhed (Jurnal Riset Informatika, 2023)
To maintain and enhance the quality of the Mobile Food Intake Control Application for Outpatients in the Hospital, usability testing must be conducted using the System Usability Scale (SUS). This research aims to evaluate usability and analyze user-friendliness for further action by the Hospital. The respondents consist of 138 outpatient patients. Testing is carried out by requesting respondents to perform scenarios on the Mobile Food Intake Control Application, observed directly by the examiner. Subsequently, respondents fill out a questionnaire containing ten statements with Likert scale responses. The average SUS score of 87.0471 indicates excellent acceptance of the application, and the user rating suggests that the application meets user expectations sufficiently. However, user speed in using the application and focusing on its features are still considered normal, and the error rate falls within acceptable limits.